Multi-band polarization imaging and image processing in sea fog environment - Liu, Nan; Fu, Qiang; Guo, Hongrui; Wang, Longxiao; Tai, Yang; Liu, Yi; Liu, Zhuang; Shi, Haodong; Zhan, Juntong; Zhang, Su; Liu, Jiazhuo (Frontiers in Physics, 2023)
Considering the advancement in marine research in recent years, studies on the identification of offshore scenery are becoming popular globally. In this study, multiband polarimetric imaging is presented to address the deficiencies of the previous single-band study. Polarization imaging experiments of sea fog and non-sea fog in an indoor simulated environment are carried out and compared and analyzed by establishing an artificial simulation system to characterize the sea fog concentration by optical thickness with different concentrations of sea fog environment as the medium. The polarization information of each waveband converted by Stokes parametric is then brought into the two-dimensional discrete wavelet algorithm for image fusion processing. The findings indicate that when the optical thickness of sea fog increases, the polarized light in the chaotic medium recedes and the effect of the image blurs. Finally, after the image fusion process, the contrast of the image is improved and the detail of the target contour is obvious, which proves that the method has good robustness under the low signal-to-noise ratio of the sea fog environment. This